A Bolus Dose of Ketamine Reduces the Amplitude of the Transcranial Electrical Motor-evoked Potential: A Randomized, Double-blinded, Placebo-controlled Study. Issue 3 (July 2021) - Furutani, Kenta; Deguchi, Hiroyuki; Matsuhashi, Mari; Mitsuma, Yusuke; Kamiya, Yoshinori; Baba, Hiroshi
Abstract : Background: A low-dose bolus or infusion of ketamine does not affect transcranial electrical motor-evoked potential (MEP) amplitude, but a dose ≥1 mg/kg may reduce MEP amplitude. We conducted a randomized, double-blinded, placebo-controlled study to evaluate the effect of ketamine (1 mg/kg) on transcranial electrical MEP. Methods: Twenty female patients (aged 12 to 18 y) with adolescent idiopathic scoliosis scheduled to undergo posterior spinal fusion were randomly allocated to receive ketamine or saline. General anesthesia was induced and maintained with continuous infusions of propofol and remifentanil. MEP was elicited by supramaximal transcranial electrical stimulation. MEP recordings were obtained at baseline and then at 2, 4, 6, 8, and 10 minutes after administration of ketamine (1 mg/kg) or saline (0.1 ml/kg). The primary endpoint was the minimum relative MEP amplitude (peak-to-peak amplitude, % of baseline value) recorded from the left tibialis anterior muscle. The baseline amplitude recorded before test drug administration was defined as 100%. Results: Medians (interquartile range) minimum MEP amplitudes in the left tibialis anterior muscle in the ketamine and saline groups were 26% (9% to 34%) and 87% (55% to 103%) of the baseline value, respectively ( P <0.001). MEP amplitudes in other muscles were significantly reduced by ketamine. The suppressive effect of ketamine lasted for at least 10 minutes in each muscle. Conclusion: A 1-mg/kg bolus dose of ketamine can reduce MEP amplitude. Anesthesiologists should consider the dosage and timing of intravenous ketamine administration during MEP monitoring. Abstract : Supplemental Digital Content is available in the text.